Nutritional assessment of critically ill patients: validation of the modified NUTRIC score. Issue 3 (March 2018) - de Vries, Manon; Koekkoek, WAC; Opdam, Marieke; van Blokland, Dick; van Zanten, Arthur
Abstract Background/objectives In order to identify critically ill patients with high nutritional risk the modified NUTrition Risk in the Critically ill (mNUTRIC)-score was developed. This score aims to identify patients that will benefit from nutritional interventions. Few data are available on its validity. In The Netherlands, the MUST-score, a nutritional assessment tool for non-ICU patients, is commonly used in the ICU. To validate the mNUTRIC-score in Dutch ICU patients and compare its prognostic performance with the MUST-score. Subjects/methods A single-center retrospective cohort study among 475 mechanically ventilated patients. Prognostic performance of the mNUTRIC and MUST-scores were assessed and compared for discriminative abilities for 28-day mortality and prolonged mechanical ventilation (>2 days). Results The discriminative ability of the mNUTRIC-score for 28-day mortality is (ROC-AUC) 0.768 (95% CI 0.722–0.814) with an associated LR+ of 1.73 (95% CI 1.53–1.95) and LR− of 0.24 (95% CI 0.14–0.39) when comparing low with high (>4) scores. Comparing low with high MUST-scores (>1) a ROC-AUC of 0.513 (95% CI 0.445–0.587) and LR+ of 1.05 (95%CI 0.77–1.45) and LR− of 0.97 (95% CI 0.71–1.17) for mortality were found. The discriminative ability for prolonged ventilation was 0.666 (95% CI 0.616–0.716) and 0.532 (95% CI 0.469–0.594) for the mNUTRIC and MUST-scores, respectively. Conclusions The prognostic performance of the mNUTRIC-score for 28-day mortality is fair and comparable to other validation studies. The association with prolonged ventilation was not confirmed by our results. The mNUTRIC-score has better performance than the commonly used MUST-score. Therefore, we suggest abandoning use of the MUST-score and to recommend introduction of the mNUTRIC-score for the nutritional risk assessment of critically ill patients.